Turnover intention and its associated factors among nurses: a multi-center cross-sectional study - Liu, Yang; Duan, Yinglong; Guo, Meiying (Frontiers in Public Health, 2023)
Aim The purpose of our study was to assess the turnover intention of nurses in China and examine the associated factors. Background Since the world population ages, the demand for nurses has kept growing, and the shortage of nurses and high turnover rates are concerned with the quality of care. Thus, understanding nurses' turnover intention and the relevant factors could provide nurse managers with strategies to address the modifiable factors to decrease the turnover rate of nurses. Methods A multi-center cross-sectional study was conducted on a total of 1,854 nurses working in 15 hospitals in China. Data were collected using a self-designed demographic questionnaire, the Turnover Intention Scale, the Job Satisfaction Scale, the Pay Level Satisfaction Scale, the Interpersonal Conflict at Work Scale, and a single question on the sense of belonging to the hospital. Results Most nurses (n = 1286, 69.4%) had a high level of turnover intention. Multilevel logistic regression analysis demonstrated that nurses being single (OR = 1.366, p < 0.05), with a junior college or below (OR = 0.381, p < 0.01), being a clinical nurse (OR = 1.913, p < 0.01), having higher pay level (OR = 0.596, p < 0.001), having higher job satisfaction (OR = 0.406, p < 0.001), having conflicts with colleagues (OR = 1.400, p < 0.05), and having a higher sense of belonging to the hospital (OR = 0.532, p < 0.001) proved to affect nurses' turnover intention. Conclusion This study extended the knowledge about the factors associated with nurses' intention to leave, which led to the turnover of nurses, and is one of the main contributors to the current shortage of nurses. Implications for nursing management This study provided new approaches to decreasing the turnover rate of nurses. Effective management strategies may mitigate nurses' turnover intention.